The correlation between parents interaction conflict with online game addiction in adolescents - Kurnia, Iqlima Dwi; Ardi, Bangun Mukti; Krisnana, Ilya; Nastiti, Aria Aulia; Rithpo, Pratuma; Arief, Yuni Sufyanti (Jurnal Ners, 2023)
Introduction: The prevalence of online game addiction has increased among adolescents in Indonesia. This study aimed to analyze the correlation between parent conflict and online game addiction among adolescents. Methods: This study used a cross-sectional, correlational design. The inclusion criteria in this study were as follows: (1) adolescents between the ages of 13-19 and who were male, and (2) adolescents who were willing to become respondents. Eighty adolescents were approached according to the inclusion criteria, and 73 respondents were eligible for this study. The data collection method used was a questionnaire filled out by adolescents. The questionnaire was adapted to adolescents and to determine adolescents' perceptions of interaction conflict. Statistical analysis was performed using Spearman's rank test with α=0.05. Results: Parental interaction conflict was positively related to online game addiction among adolescents (p = 0.004). The majority of respondents who experienced online game addiction in the fair category had low interaction conflicts with their parents. Conclusions: Conflict of interaction with parents can cause adolescents to become addicted to online games. Parents are expected to engage in good interactions in accordance with the stages of adolescent development. Parents should be able to complete their problem interactions well.